The Effects of a Structured Resiliency Program on Indicators of Burnout in Medical Residents - Riese, Amy; Brennan, Julie; Lynch, Denis; Nowak, Jordin; McGrady, Angele (Translation: The University of Toledo Journal of Medical Sciences, 2024)
Because of the well documented burnout and stress experienced by medical residents, the Accreditation Council for Graduate Education (ACGME) has directed training programs to address these issues in their residents. The current study describes a resiliency enhancement program administered to residents from differing residencies. Method: Residents received group-based sessions focusing on awareness of stress reactions, mindfulness, cognitive coping skills and balancing life and work. All sessions were interactive. The training occurred over a 9-month time span. Residents provided informed consent so that data could be collected. The percentage of burnout was calculated based on one indicator (high emotional exhaustion, high depersonalization, or low personal accomplishment using the Maslach Burnout Scale). Standardized assessment instruments were administered at the beginning (September) and the end of the program (May) to assess the impact of the intervention. Residents were in training at a medium-sized academic medical center. They came from urology, internal medicine, emergency medicine and neurology training programs. Eighteen female and 51 male residents participated. Results: Baseline rates of burnout were as follows: urology residents, 89%; internal medicine, 73%; neurology, 50%; emergency medicine, 22%. There was a significant decrease in perceived stress for the overall group following the intervention. Residents who significantly improved on mindfulness measures also showed significant improvement on resiliency, stress, and personal accomplishment scores. Residents who significantly lowered perceived stress also lowered emotional exhaustion, depersonalization, and increased resiliency and compassion satisfaction. Discussion: This study demonstrated that a resiliency enhancement program and data collection after IRB approval is feasible and effective during medical residency. Based on our analysis, mindfulness, and cognitive skills to reduce perceptions of stress seem to be critical components. Future research is necessary to identify elements of the program most relevant to specific residencies.